Suggestion of an inverse relationship between perception of occupational risks and work-related injuries - Ricardo Cordeiro
Worker perception of risk influences worker behavior and consequently exposure to risks. However, an inverse relationship between perception of occupational risks and work-related injuries has not yet been clearly established. A matched case-control was performed aiming to investigate possible differences in perception of occupational risks between workers who had suffered occupational injuries and those who had not. Cases were defined as all 93 workers from a large metallurgical factory in southeastern Brazil, who had suffered occupational injuries during the year 1996. Controls were 372 workers who had not suffered occupational injuries, matched on the basis of the factory sector and jobs performed. Assessment of occupational risk perception was performed by asking the workers to fill out a questionnaire consisting of questions on specific risks related to problems in work relations, work per se, and mode of production. The findings suggest that the degree of perception that workers with occupational injuries have of some occupational risks is lower than that of their non-injured coworkers.